2006
DOI: 10.1103/physrevlett.97.155901
|View full text |Cite
|
Sign up to set email alerts
|

Proton Diffusion Mechanism in AmorphousSiO2

Abstract: We study proton diffusion in amorphous SiO2 from the atomic scale to the long-range percolative regime. Ab initio molecular dynamics suggest that the dominant atomic process consists in cross-ring interoxygen hopping assisted by network vibrations. A statistical analysis accounting for the disorder in amorphous SiO2 yields relations between transition energies and interoxygen distances for both cross-ring and nearest-neighbor hopping. The percolative regime is then addressed through large-size model systems re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 31 publications
(34 reference statements)
3
32
0
Order By: Relevance
“…19 Reversible motion of protons in SiO 2 has been demonstrated by memory effects occurring in Si/ SiO 2 / Si devices, where protons shuttle through the SiO 2 from one Si layer to the other. 20 DFT calculations on transport of protons in SiO 2 predict an activation energy of about 0.5 eV, 21 which is close to the 0.6 eV activation energy found in bias-stress experiments on different organic semiconductors. 8 This strongly supports our proposition that proton motion in the SiO 2 causes the bias-stress effect.…”
Section: Proton Migration Mechanism For the Instability Of Organic Fimentioning
confidence: 55%
“…19 Reversible motion of protons in SiO 2 has been demonstrated by memory effects occurring in Si/ SiO 2 / Si devices, where protons shuttle through the SiO 2 from one Si layer to the other. 20 DFT calculations on transport of protons in SiO 2 predict an activation energy of about 0.5 eV, 21 which is close to the 0.6 eV activation energy found in bias-stress experiments on different organic semiconductors. 8 This strongly supports our proposition that proton motion in the SiO 2 causes the bias-stress effect.…”
Section: Proton Migration Mechanism For the Instability Of Organic Fimentioning
confidence: 55%
“…According to their calculations, the size of the percolation cluster approaches infinity when all the sites separated by an energy barrier less than 0.5 eV are connected. 30 This activation energy of about 0.5 eV for longrange diffusion of protons is close to the 0.6 eV activation energy found in bias-stress experiments on different organic semiconductors. 11 This strongly suggests that proton motion in the SiO 2 determines the dynamics of the bias-stress effect.…”
Section: Proton Migration Mechanism For the Bias-stress Effectmentioning
confidence: 55%
“…The mobility of protons in amorphous SiO 2 has been studied by directly sensing charge displacements, indicating hopping transport of protons with hopping lengths well beyond first-neighbor oxygen distances. 29 In a theoretical study, Godet and Pasquarello 30 showed that protons usually bind to bridging O atoms in Si-O rings that become threefold coordinated with O-H + bond lengths of about 1 Å. The hopping mechanism involves a transient complex, in which a proton is shared by two O atoms of different rings.…”
Section: Proton Migration Mechanism For the Bias-stress Effectmentioning
confidence: 99%
“…Reversible motion in SiO 2 is the basis of memory effects in Si/SiO 2 /Si devices, where protons shuttle through the SiO 2 layer from one Si layer to the other on a time scale of seconds to thousands of seconds, [47,48] i.e., on a similar time scale as the bias-stress effect in OFETs. DFT calculations predict an activation energy for proton diffusion in SiO 2 of E d = 0.5 eV, [49] which is close to the E a ≈ 0.6 eV activation energy for the bias-stress effect measured in OFETs with different organic semiconductors. [30] Based on these considerations, the following mechanism for the bias-stress effect in p-type OFETs is proposed: [50,51] 1.…”
Section: Potentiometry At the Sio 2 Surfacementioning
confidence: 78%